High-voltage stimulation over the human spinal cord: sources of latency variation. Issue 2 (February 1989) - Plassman, B L; Gandevia, S C
Abstract : Percutaneous electrical stimuli (up to 600 V) were applied over the cervical spinal cord to evoke responses in the biceps brachii and thenar muscles. Cathodal stimulation over the C7 spinous process was more effective than anodal stimulation or stimulation over the C5 or C3 spinous process. As the stimulus intensity was increased, the response amplitude increased and the latency decreased. When progressively higher levels of supramaximal stimuli were delivered the latency often decreased further. The shortest latencies evoked by stimulation over the C7 spinous process were close to the latencies of the responses evoked by supramaximal stimulation near Erb's point. Thus, with this type of stimulation, the site of nerve activation changes with different stimulus intensities. The variability in latency introduced by distal spread of the site of activation will affect measurements of central motor conduction time and should be considered in the diagnostic use of this technique.